HUBUNGAN AKTIFITAS FISIK DENGAN INDEKS MASSA TUBUH PADA ANAK USIA SEKOLAH 7 samapai 12 DI MASA PANDEMI COVID 19 (SDN GROGOL 2) - Bintang Furtuna, Intan Syah (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
Due to low physical activity, it causes an increase in the factor of increasing body mass index (BMI). This study aims to determine the relationship between physical activity and body mass index of school age children 7 until 12 at SDN Gorogol 2, Jombang Regency. This type of research is a quantitative research with a cross sectional approach. The population in this study were school age children 7 until 12 years at SDN Grogol 2 Jombang. Data was collected using weight scales, microtoie, and the PAQ C questionnaire. Sampling was done by using the sample probability method in which a population of 130 students was obtained with a sample of 99 samples. The data analysis technique used Fisher's technique. The results showed that of the 99 students the majority had fairly light physical activity as many as 64 people (64.6 pecent). Based on the results of the Fisher Excat Test conducted using the crosstab method, a significant value of 0.010 was obtained (p value less than 0.05). This shows that there is a relevant relationship between Body Mass Index (BMI) and physical activity in grade 1 until 6 students.